The EU's responsibility in the securitization of Eastern Europe: Prospects for using the full potential of the CSDP in the region - Gabriela Cristina Șpaiuc (CES Working Papers, 2021)
The level of ambition and strategic autonomy of the European Union in the global approach of conflicts and crises was tested in the context of unsolved conflicts which characterised the security environment in the East European neighbourhood area. We set out to analyse the main strategies, security policies and tools used by the EU in relationship with the countries of the Eastern Partnership, in response to various kinds of security problems in the region. The coherence of the European policies regarding the role of securitization of countries from the Eastern border of Europe depends on the use of the whole potential of legal instruments set out in the treaties. At the same time, the Union relevance is defined by the adaptation of these policies to the security needs resulted from the political instability and the military threats to which the countries of this region are exposed.
Keywords: 330; European Union; Eastern Partnership; security; hybrid threats; CSDP